Ecological segregation drives fine-scale cytotype distribution of Senecio carniolicus in the Eastern Alps - Hülber, Karl; Sonnleitner, Michaela; Flatscher, Ruth; Berger, Andreas; Dobrovsky, Rainer; Niessner, Sophie; Nigl, Thomas; Schneeweiss, Gerald M; Kubešová, Magdalena; Rauchová, Jana; Suda, Jan; Schönswetter, Peter (Preslia, 2009)
In order to uncover patterns and processes of segregation of co-existing cytotypes, we investigated a zone in the eastern Alps (Austria) where diploid and hexaploid individuals of the alpine herb Senecio carniolicus Willd. (Asteraceae) co-occur. Linking the fine-scale distribution of cytotypes to environmental and spatial factors revealed segregation along an ecological gradient, which was also reflected in the cytotype-associated plant assemblages. Compared to diploids, hexaploids are found in more species-rich and denser communities. This may be due to their better competitive ability and lower tolerance of abiotic stress compared to the diploids. The lack of any intermediate cytotypes suggests the presence of strong reproductive isolation mechanisms, whose nature is, however, elusive.